P228 Comparing cardiometabolic risk indicators between adults post-hospitalisation with COVID-19 and healthy controls. (11th November 2022) - Bakali, M; Yates, T; Steiner, MC; Evans, RA
Abstract : Introduction and Objectives: Adults with cardiometabolic disease including diabetes, hypertension and obesity are associated with more severe acute coronavirus disease 2019 (COVID-19). The aim of this exploratory cross-sectional study was to compare detailed cardiometabolic risk profiling between adult survivors of severe COVID-19 and healthy controls. Methods: Eligible patients in the COVID-19 group were between 3–7 months post-discharge from hospital with acute COVID-19 and recruited through a longitudinal cohort study (PHOSP-COVID). Historical adult age and sex matched healthy controls with no pre-existing conditions recruited prospectively to a different study were used as a comparator group. Cardiometabolic risk indicators were assessed including measures typically measured in clinical care (resting blood pressure, fasting glucose, BMI, waist circumference), alongside more detailed assessments including central and peripheral arterial stiffness using pulse wave velocity (PWV), Homeostatic Model Assessment for Insulin Resistance (HOMA-IR) and an oral glucose tolerance test (OGTT). Data are presented as mean [SD] or median [interquartile range] depending on distribution. Results: 38 adults recovering from severe COVID-19 (mean [SD] age 62 [9] years, 45% male) and 17 healthy controls (mean [SD] age 62 [9] years, 53% male) completed the study ( table 1 ). BMI and other clinical measures (blood pressure, fasting glucose, HbA1C) indicated a higher cardiometabolic risk profile in adults post-COVID-19 compared to healthy controls – Table 1 . Carotid-femoral and brachial-ankle PWV were higher in the adults post-COVID-19 compared to the healthy controls and similarly insulin resistance assessed by HOMA-IR was also higher. Exercise capacity was reduced in the post-COVID-19 group compared to the healthy controls. Conclusions: This exploratory cross-sectional study shows that routinely used clinical tests of cardiometabolic risk indicate higher future risk for adults post-COVID compared to healthy controls. More detailed measures of cardiometabolic risk support this finding. It is unclear whether acute COVID-19 further contributes to pre-existing cardiometabolic risk. However, our small exploratory study supports the need for interventions such as aerobic exercise training which are proven to reduce aortic stiffness in adults with cardiometabolic disease or who are at future risk of cardiometabolic disease.